Cannabis Use Is Associated With Increased Risk of Post–Endoscopic Retrograde Cholangiopancreatography Pancreatitis: Analysis of the US Nationwide Inpatient Sample Database, 2004–2014. Issue 9 (October 2018) - Njei, Basile; Sharma, Prabin; McCarty, Thomas R.; Singh, Manpreet; Haque, Lamia; Aslanian, Harry R.; Jamidar, Priya; Muniraj, Thiruvengadam
Abstract : Objective: The aim of this study was to investigate the impact of cannabis on post–endoscopic retrograde cholangiopancreatography pancreatitis (PEP). Methods: The US Nationwide Inpatient Sample was queried to identify patients who underwent endoscopic retrograde cholangiopancreatography pancreatitis from 2004 to 2014. Cannabis use was identified by International Classification of Diseases, Ninth Edition codes, and patients in remission were excluded. Poisson regression models were used to derive adjusted incidence risk ratios (IRRs) for outcomes. Results: Among 37, 712 patients with PEP, 0.4% had documented cannabis use disorder. From 2004 to 2014, the rate of PEP and cannabis use increased (8.9%–11.0% [ P < 0.01] and 0.20%–0.70% [ P < 0.01], respectively). Univariate analysis demonstrated cannabis was associated with increased risk of PEP (IRR, 1.70; 95% confidence interval [CI], 1.50–1.90; P < 0.01). On multivariate analysis, cannabis use was an independent predictor of PEP (IRR, 1.2; 95% CI, 1.1–1.4; P = 0.004). Cannabis was not associated with in-hospital death (IRR, 0.15; 95% CI, 0.02–1.04; P = 0.06) but was associated with shorter hospital stay (IRR, 0.96; 95% CI, 0.94–0.98; P < 0.001) and lower costs (IRR, 0.91; 95% CI, 0.91–0.92; P < 0.001). Conclusions: Cannabis use was associated with an increase in PEP without significant increase in mortality. Abstract : Supplemental digital content is available in the text.